Risk assessment of Salmonella in pork in Hanoi, Vietnam - Luu Quoc Toan; Hung Nguyen-Viet; Bui Mai Huong (2013)
Quantitative Microbial Risk Assessment (QMRA) was used to assess the health risk of pork meat contaminated by Salmonella spp. in Hanoi, Vietnam. A total of 72 pork samples were collected from 4 formal markets in Long Bien District, Hanoi. Salmonella spp. was analyzed by the Most Probable Number (MPN) method. A survey consisting of self-administered structured questionnaires was conducted in 210 households to determine the consumption of pork and examine cooking and eating habits. A health risk assessment was performed for 4 scenarios of cross-contamination of Salmonella spp. including contamination from raw meat to cooked food via i) hands, ii) knife, iii) cutting board, and iv) full cross-contamination. The results showed that Salmonella spp. was detected in 25% of pork samples (18/72). The concentration of Salmonella spp. varied from 100 to 27,500 per 25 grams of pork (mean: 673 per 25 grams). Pork consumption, a component of exposure assessment, was estimated by amount and frequency. The mean amount of pork consumption was estimated at 86.1 grams per person per day; mean frequency of pork consumption was 219 days per person per year. Infection risk of Salmonella spp. was from 2.1×10-4 to 4.9×10-4 by single exposure (per consumption). The annual risk was from 4.3×10-2 to 9.5×10-2. Although this study considered only one stage of exposure in the “farm to fork” chain, the findings showed that this stage is critical and represents a potential health risk for consumers. Appropriate practices for pork meat preparation and consumption at the household level need to me targeted as risk management measures.